Characterization of olivines and their metallic composition: Raman spectroscopy could provide an accurate solution for the active and future Mars missions. (30th December 2022) - Torre‐Fdez, Imanol; García‐Florentino, Cristina; Huidobro, Jennifer; Coloma, Leire; Ruiz‐Galende, Patricia; Aramendia, Julene; Castro, Kepa; Arana, Gorka; Madariaga, Juan Manuel
Abstract: The presence of olivine and its geochemical composition (forsterite/fayalite ratio) are relevant factors for the study of Mars. The use of Raman spectrometers in the Mars 2020 and future missions opens new possibilities to assess the Mg/Fe ratios in the analyzed olivine bearing rocks. On the one hand, its presence indicates approximately where and when Mars had volcanic activity, due to the partial weathering of this mineral into other secondary minerals. On the other hand, the forsterite and fayalite content of olivine can be used to study the origin and evolution of its parent magma, since this mineral is one of the first to crystallize from it. In order to properly study the forsterite and fayalite ratio of olivines, this work proposes a new calibration model using Raman spectroscopy, doing a thorough literature review of previous studies in order to improve the calibration quality. The proposed model improves greatly the accuracy and uncertainty associated with the final result of forsterite and fayalite (around 2%) compared to those published earlier in the literature (around or above 10%). Using the new model, it will be possible to assess the forsterite and fayalite ratios of Martian olivines properly, providing relevant information about their parent magma. Abstract : The presence of olivine (forsterite/fayalite ratio) is a relevant factor for the study of Mars. The use of Raman spectrometers in the Mars 2020 and future missions opens new possibility to assess the Mg/Fe ratios in the analyzed olivine bearing rocks. This work proposes a new calibration model using Raman spectroscopy, which improves greatly the accuracy and uncertainty associated to the final result of forsterite and fayalite compared to other models published earlier.